Bone Marrow-sparing Intensity Modulated Radiation Therapy With Concurrent Cisplatin For Stage IB-IVA Cervical Cancer: An International Multicenter Phase II Clinical Trial (INTERTECC-2) - Mell, Loren K; Sirák, Igor; Wei, Lichun; Tarnawski, Rafal; Mahantshetty, Umesh; Yashar, Catheryn M; McHale, Michael T; Xu, Ronghui; Honerkamp-Smith, Gordon; Carmona, Ruben; Wright, Mary; Williamson, Casey W; et al. (International journal of radiation oncology, biology, physics, 2017)
PURPOSE: To test the hypothesis that intensity modulated radiation therapy (IMRT) reduces acute hematologic and gastrointestinal (GI) toxicity for patients with locoregionally advanced cervical cancer. METHODS AND MATERIALS: We enrolled patients with stage IB-IVA cervical carcinoma in a single-arm phase II trial involving 8 centers internationally. All patients received weekly cisplatin concurrently with once-daily IMRT, followed by intracavitary brachytherapy, as indicated. The primary endpoint was the occurrence of either acute grade ≥3 neutropenia or clinically significant GI toxicity within 30 days of completing chemoradiation therapy. A preplanned subgroup analysis tested the hypothesis that positron emission tomography-based image-guided IMRT (IG-IMRT) would lower the risk of acute neutropenia. We also longitudinally assessed patients' changes in quality of life. RESULTS: From October 2011 to April 2015, 83 patients met the eligibility criteria and initiated protocol therapy. The median follow-up was 26.0 months. The incidence of any primary event was 26.5% (95% confidence interval [CI] 18.2%-36.9%), significantly lower than the 40% incidence hypothesized a priori from historical data (P=.012). The incidence of grade ≥3 neutropenia and clinically significant GI toxicity was 19.3% (95% CI 12.2%-29.0%) and 12.0% (95% CI 6.7%-20.8%), respectively. Compared with patients treated without IG-IMRT (n=48), those treated with IG-IMRT (n=35) had a significantly lower incidence of grade ≥3 neutropenia (8.6% vs 27.1%; 2-sided χ2P=.035) and nonsignificantly lower incidence of grade ≥3 leukopenia (25.7% vs 41.7%; P=.13) and any grade ≥3 hematologic toxicity (31.4% vs 43.8%; P=.25). CONCLUSIONS: IMRT reduces acute hematologic and GI toxicity compared with standard treatment, with promising therapeutic outcomes. Positron emission tomography IG-IMRT reduces the incidence of acute neutropenia.
Keywords: radiosenzibilizující látky; Radiotherapy, Image-Guided; Gastrointestinal Tract; Bone Marrow; Cisplatin; cisplatina; Female; Adenocarcinoma; neutropenie; Middle Aged; brachyterapie; protinádorové látky; spinocelulární karcinom; Antineoplastic Agents; Feasibility Studies; Organ Sparing Treatments; Neutropenia; léčba šetřící orgány; nádory děložního čípku; adenokarcinom; Radiation-Sensitizing Agents; Uterine Cervical Neoplasms; Radiotherapy Dosage; gastrointestinální trakt; ženské pohlaví; Carcinoma, Squamous Cell; radioterapie s modulovanou intenzitou; studie proveditelnosti; kostní dřeň; celková dávka radioterapie; Radiotherapy, Intensity-Modulated; incidence; lidé středního věku; Incidence; Chemoradiotherapy; radioterapie řízená obrazem; lidé; Humans; Brachytherapy; chemoradioterapie